Metformin in patients with and without diabetes: a paradigm shift in cardiovascular disease management - Fei Luo; Avash Das; Jingfei Chen; Panyun Wu; Xiangping Li; Zhenfei Fang (2019)
With an increasing global burden of coronary artery disease (CAD), early detection and timely management of risk factors are crucial to reduce morbidity and mortality in such patients. Diabetes mellitus (DM) is considered an independent risk factor for the development of CAD. Metformin, an anti-diabetic drug, has been shown in pre-clinical and clinical studies, to lower the cardiovascular events in the DM patients. Growing evidence suggests that metformin has a protective effect on coronary artery beyond its hypoglycemic effects. Given its global availability, route of administration and cost, metformin provides an alternate/additional therapeutic option for primary and secondary prevention of CAD in DM and non-diabetics alike. Future prospective cohort-based studies and randomized clinical trials are needed to identify 'at-risk' population who may potentially benefit from metformin.